Subject-Verb Agreement Analysis in Prabowo Subianto’s Interview as President-Elect at the Qatar Economic Forum - Afore Tahir Harefa; Feliks Rejeki Sotani Zebua; Martin Ifolala Zamasi; Yarlin Harefa (Departement of Mathematics Education, 2024)
This study analyzes the use of subject-verb agreement in Prabowo Subianto’s interview as president-elect at the Qatar Economic Forum. The objective is to evaluate the accuracy of subject-verb agreement in his spoken English during the interview. Using qualitative content analysis, the transcript of the interview was examined to identify instances of correct and incorrect subject-verb agreement. The results indicate a consistent application of subject-verb agreement throughout the interview, with both singular and plural subjects correctly matched with their respective verbs. This consistency contributes to the clarity and professionalism of the communication. Despite the spontaneous nature of spoken language, which often allows for grammatical leniency, Subianto's use of subject-verb agreement was found to be highly accurate. These findings highlight the importance of grammatical precision in spoken English, especially in formal settings.